2015
DOI: 10.1177/2332858415599972
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Influence on Educational Attainment

Abstract: Recent studies have begun to uncover the genetic architecture of educational attainment. We build on this work using genome-wide data from siblings in the National Longitudinal Study of Adolescent to Adult Health (Add Health). We measure the genetic predisposition of siblings to educational attainment using polygenic scores. We then test how polygenic scores are related to social environments and educational outcomes. In Add Health, genetic predisposition to educational attainment is patterned across the socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
97
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 58 publications
4
97
0
2
Order By: Relevance
“…Most existing studies work with an older, less predictive polygenic score based on the results of Rietveld et al (2013). Domingue et al (2015) demonstrate that this polygenic score predicts educational attainment in the Add Health study, and that this association appears to operate separately from childhood environments since it predicts higher education within sibling groups. Indeed, Rietveld et al (2014) find similar coefficients on a related polygenic score using either within-family variation or within and across family variation.…”
mentioning
confidence: 76%
“…Most existing studies work with an older, less predictive polygenic score based on the results of Rietveld et al (2013). Domingue et al (2015) demonstrate that this polygenic score predicts educational attainment in the Add Health study, and that this association appears to operate separately from childhood environments since it predicts higher education within sibling groups. Indeed, Rietveld et al (2014) find similar coefficients on a related polygenic score using either within-family variation or within and across family variation.…”
mentioning
confidence: 76%
“…GRS derived from PGC results have been widely used in psychiatric research for generating patient strata, exploring diagnostic boundaries, identifying cognitive and behavioral correlates of genetic risk that predate clinical disorders, and evaluating the validity of putative cognitive or imaging phenotypes (47). Many social scientists have embraced the approach, seeing opportunities to study how genetic factors interact with the social environment (e.g., socio-economic status) to influence health and broader outcomes (48). …”
Section: Pgc An Agendamentioning
confidence: 99%
“…1000 Genomes phase 3), hence this issue is less important. Moreover, simulations found that the effect of LD decay on true causal variants was null to negligible [24]. The present study, by focusing only on the most significant hits, increased the likelihood of hitting on or very close to causal variants, hence reducing the artifact of LD decay.…”
Section: Discussionmentioning
confidence: 65%
“…It is sensitive to coverage and in older studies using low coverage genomic data (e.g. 1000 Genomes phase 1), it was found to reduce the reproducibility of findings [24]. However, contemporary GWAS use higher coverage data (e.g.…”
Section: Discussionmentioning
confidence: 99%